HISTORICAL GEOGRAPHY CLASSIFICATION OF KITAB’S BEKLIK, AN OASIS OF EASTERN KASHKADARYA (Journal of Universal Science Research, 2023)
The Kashkadarya oasis is was important part of the Bukhara Emirate, and the cities of the oasis played an important role in the socio-political, economic and cultural life of the emirate. One of such important areas is the last medieval Kitab principality, which is covered in this article about its historical-geography, history, socio-economic and political history, on the basis of scientific sources and memoirs and diaries of Russian tourists.